Fabrication and characterization of FAST sintered micro/nano boron carbide composites with enhanced fracture toughness. Issue 15 (December 2020) - Dai, Jingyao; Singh, Jogender; Yamamoto, Namiko
Abstract: Toughening of boron carbide (B4 C) without hardness degradation, was achieved by hierarchical structures consisting of B4 C micro-grains, titanium diboride (TiB2 ) grains, and graphitic phases along B4 C grain boundaries. Such hierarchical structures were uniquely achieved by co-sintering of B4 C micro-powder and carbon-rich B4 C nano-powder, in situ formation of TiB2, and by utilizing the short sintering time of field-assisted sintering technology. Toughening mechanisms observed after micro-indentation include crack deflection and delamination of graphite platelets, micro-crack toughening and crack deflection/bridging by TiB2 grains. Fracture toughness enhancement was achieved while maintaining hardness: 4.65 ± 0.49 MPa m 1/2 fracture toughness and 31.88 ± 1.85 GPa hardness for a micro/nano B4 C-TiB2 composite (15 vol% TiB2 and 15 vol% B4 C nano-powders) vs . 2.98 ± 0.24 MPa m 1/2 and 32.46 ± 1.67 GPa for a reference micro B4 C sample. In future, macro-scale mechanical testing will be conducted to further evaluate how these micro-scale hierarchical structures can be translated to macro-scale mechanical properties.